The Traditional Medicine Practitioner’s Concept of Cancer, Herbal Medicine use and the Patients Perceived Benefits (Clinical outcomes) in Selected Districts of Central Uganda: An Exploratory Study Protocol - Asiimwe, John Baptist; Nagendrappa, Prakash B.; Atukunda, Esther C.; Nambozi, Grace; Ogwang, Patrick E.; Sarki, Ahmed M.; Kamatenesi, Maud M. (Research Square, 2021)
In sub-Saharan Africa, herbal medicine for cancer is dispensed by traditional medicine practitioners (TMPs) to a large extent, who may not have adequate knowledge about the disease and this has been found to contribute to the late presentation of cancer patients to clinics and hospitals leading to poor patient outcomes.